A residual heat compensation based scan strategy for powder bed fusion additive manufacturing. (August 2020) - Yeung, H.; Lane, B.
Abstract: Typical scan strategies for laser powder bed fusion (LPBF) additive manufacturing systems apply a constant laser power and scan speed. Localized preheating from adjacent scan paths (residual heat) result in inconsistent melt-pool morphology. A new control approach is proposed which compensates the residual heat through laser power adjustment. A model called residual heat factor (RHF) is developed to 'quantify' the residual heat effect, and laser power is controlled proportional to this RHF. Experiments are conducted on a custom-controlled LPBF testbed on nickel-alloy (IN625) bare plate, and the effects of this unique scan strategy are investigated by in-situ melt-pool monitoring.